Banking without interest - Jana Ilieva; Natasha Ristovska; Saso Kozuharov (UTMS Journal of Economics, 2017)
In recent years, there has been increased global awareness of Islamic finance. This topic is mainly opened with respect to the great financial crisis that mostly hit the banking system and the financial markets and caused many bank bankruptcies and state interventions. This paper analyzes the basic principles of Islamic banking. The absolute prohibition of receiving and giving interest (Riba) and profit-and-loss sharing (PLS) paradigms are elaborated in detail; they are primarily based on mudarabah (profit-sharing) and musyarakah (joint venture) concepts which nowadays are becoming an accepted way of doing business in several Western multinational banks. An overall comparison of the advantages of Islamic vs. conventional banking is also given. Islamic finance technology solutions have matured and they will face various challenges in the following decades, due to conventional banks offering, increasingly, Islamic products. The need for a more comprehensive environment and regulatory framework is emphasized, so that Islamic banking development can be ensured.
Keywords: G20; K22; K33; 330; Islamic; law; finance; banks; growth